Evaluation of physico-mechanical, chemical properties and cytotoxicity of fabricated glass ionomer nano zirconia-silica- hydroxyapatite hybrid material - Sajjad, Arbaz (2020)
The aim of this study was to synthesize and characterize a nano zirconia-silicahydroxyapatite (nanoZrO2-SiO2-HA) composite and to investigate the effects of adding nanoZrO2-SiO2-HA to a conventional glass ionomer cement (cGIC). NanoZrO2-SiO2-HA composite was synthesized using a one-pot sol-gel technique, which was then characterized using scanning electron microscope (SEM), transmission electron microscope (TEM), fourier transform infrared spectroscopy (FTIR) and x-ray diffraction (XRD). Following the characterization studies, further investigations were carried out after addition of nanoZrO2-SiO2-HA to cGIC (GIC nanoZrO2-SiO2-HA) at varying weight percentage (~3% to 9%) to compare their mechanical properties (compressive strength, flexural strength, and fracture toughness), physical properties (surface roughness, colour stability and sorptionsolubility), chemical property (fluoride ion release) and cytotoxicity in relation to cGIC (Fuji IX). SEM and TEM images were successful in demonstrating that the particle morphology in terms of size to shape distribution was small and narrow with low agglomeration. The nano powder consisted of rod-shaped HA crystallites (~114 nm) interspersed with spherical silica (~18 nm) and zirconia (~39 nm) particles. The FTIR spectra indicated some molecular interaction presented between the nanoZrO2- SiO2-HA and GIC. The XRD diffractogram indicated the presence of peaks for ZrO2, SiO2 and HA. Compressive strength, flexural strength and fracture toughness of GIC 5%nanoZrO2-SiO2-HA was statistically higher than that of other percentages of GIC nanoZrO2-SiO2-HA and cGIC. The highest values recorded were- compressive strength (144.12  13.88 MPa), flexural strength (18.12  2.33 MPa) and fracture toughness (1.35  0.15 MPa.m1/2), leading to an increase of ~30 %, ~26 % and ~57 % respectively, as compared to cGIC. Additionally, GIC 5%nanoZrO2-SiO2-HA had a roughness profile (0.158μm ± 0.29) similar to cGIC (0.151μm ± 0.29). Overall, the color change (ΔE) values for GIC 5% nanoZrO2-SiO2-HA group were lower than those of cGIC over a 28 day period and were between slight to perceptible. The GIC 5%nanoZrO2-SiO2-HA showed highly significant difference in the mean fluoride release for all the time intervals as compared to cGIC (p ≤ 0.05). In addition, GIC 5%nanoZrO2-SiO2-HA recorded lower sorption values (23.64 ± 2.3 μgmm-3) as compared to cGIC (36.28 ± 2.6 μgmm-3) and higher solubility (66.46 ± 2.4 μgmm-3) as compared to cGIC (56.76 ± 1.6 μgmm-3). The results of cytotoxicity testing showed that GIC 5%nanoZrO2-SiO2-HA demonstrated cytotoxicity at 24 h incubation for 200 mg/ml conc. However, at 72 h incubation it exhibited lower cytotoxic response as compared to cGIC which was statistically significant (p<0.05) at 200 mg/ml concentration of the material extract. The addition of nanoZrO2-SiO2-HA to cGIC significantly enhanced its physico-mechanical, chemical properties and demonstrated a favourable cytotoxic response. Based on the results of our recently concluded study, GIC nanoZrO2-SiO2-HA has the potential to be suggested as a restorative dental material with diverse applications ranging from cavity restoration, core build-up and as a luting material.